Haiti Unbound A Spiralist Challenge to the Postcolonial Canon - Glover, Kaiama L. (Contemporary French and Francophone Cultures, 2011)
Touching on the role and destiny of Haiti in the Americas, Haiti Unbound engages with long-standing issues of imperialism and resistance culture in the transatlantic world. Glover's timely project emphatically articulates Haiti's regional and global centrality, combining vital 'big picture' reflections on the field of postcolonial studies with elegant close-reading-based analyses of the philosophical perspective and creative practice of a distinctively Haitian literary phenomenon. Providing insightful and sophisticated blueprints for the reading and teaching of the Spiralists' prose fiction, it will serve as a point of reference for the works of these authors and for the singular socio-political space out of and within which they write.